PENGEMBANGAN SEBUAH PENGAJARAN RESPONSIF BUDAYA (CRT) PADA KELAS DRAMA (SEBUAH KOLABORASI MAHASIWA DALAM PEMENTASAN DRAMA CERITA LOKAL) - Erny Selfina Nggala Hambandima (Perspektif Ilmu Pendidikan, 2021)
DEVELOPING A CULTURALLY RESPONSIVE TEACHING (CRT) ON TEACHING DRAMA ( A COLLABORATION ON STUDENTS’ LOCAL STORY DRAMA PERFORM) ESNHAbstract: This study is meant to investigate how lecturer develop a culturally responsive teaching on drama class especially students’ collaborative of local story drama perform. The problem of this research is formulated as how does the lecturer develop CRT on teaching drama? The study was stimulated by the writer’s interest to examine the CRT on a collaboration of 5th semester students’ local story drama performance by understanding the local story through drama teaching whereas nowadays teaching also touch about the local content. The research subjects are 5th semester students from 3 different classes that the writer collaborate them in a collaboration team. The writer randomly collaborate the students by means of getting them to adapt, cooperate and create their own acting to be more fearless, creative in front of the stage. A qualitative research was conducted by observing the students’ activity and watching the video documenting students’ performance. From the data result the writer found that the drama class based CRT are the students learn within the context of different culture, students being the center in teaching and learning process, students adjusted the learning with the group members and the teacher being the mediator to succeed the students’ project. The conclusion is the students enrich their knowledge of historical story from different ethnics as well as they authentically know the differences local story among them. The suggestions are the educators should convey the local content in teaching and learning process in class based culturally responsive teaching. Keywords: Developing, Culturally Responsive Teaching (CRT), Teaching Drama, Collaboration